1992
DOI: 10.1111/j.1570-7458.1992.tb01571.x
|View full text |Cite
|
Sign up to set email alerts
|

Response of the braconid parasitoid Cotesia (=Apanteles) glomerata to volatile infochemicals: effects of bioassay set‐up, parasitoid age and experience and barometric flux

Abstract: Upon initiating a research project on the role of volatile infochemicals in the tritrophic system Cotesia (= Apanteles) glomerata (L.) ‐ Pieris brassicae (L.) ‐ cabbage, a bioassay was developed to investigate the response of C. glomerata. The bioassay should be effective in terms of high responsiveness and minimum variability and constructed through a comparative approach. Twenty seven treatments, organized in a factorial randomized block design, compared the effect of three bioassay set‐ups (glasshouse fligh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
111
1
2

Year Published

1997
1997
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 146 publications
(119 citation statements)
references
References 28 publications
5
111
1
2
Order By: Relevance
“…This indicates that subtle differences in volatile profiles of uninfested plants could be important in the attractivity of these plants for D. semiclausum. Brussels sprout plants damaged by hosts are more attractive for the parasitoids Cotesia glomerata, C. rubecula, and C. plutellae than artificially damaged or intact Brussels sprout plants (Steinberg et al, 1992(Steinberg et al, , 1993Blaakmeer et al, 1994;Geervliet et al, 1996;Shiojiri et al, 2000). A recent study by Ohara et al (2003) showed that D. semiclausum females were attracted by the odor blends of uninfested and infested cruciferous plants.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that subtle differences in volatile profiles of uninfested plants could be important in the attractivity of these plants for D. semiclausum. Brussels sprout plants damaged by hosts are more attractive for the parasitoids Cotesia glomerata, C. rubecula, and C. plutellae than artificially damaged or intact Brussels sprout plants (Steinberg et al, 1992(Steinberg et al, , 1993Blaakmeer et al, 1994;Geervliet et al, 1996;Shiojiri et al, 2000). A recent study by Ohara et al (2003) showed that D. semiclausum females were attracted by the odor blends of uninfested and infested cruciferous plants.…”
Section: Discussionmentioning
confidence: 99%
“…Because associative learning often increases the response of parasitoids to host-related volatiles (Vet and Groenewold 1990;Turlings et al 1991;Steinberg et al 1992;Conti et al 1997;Drukker et al 2000;SantolamazzaCarbone et al 2004), we investigated the effects of experience on A. iole response to HIPVs. Specifically, we asked: (1) Do female and male A. iole antennae respond differentially to HIPVs?…”
Section: Introductionmentioning
confidence: 99%
“…Foraging female Cotesia glomerata (L.) are strongly attracted to cabbage plants with Pieris brassicae (L.) feeding damage (Steinberg et al 1992 There was a higher consumption of foliage by normal larvae compared with sterile larvae when larvae were allowed to pupate. This was attributed to a higher mortality rate among sterile larvae over their entire developmental period.…”
Section: Discussionmentioning
confidence: 99%